SPATIAL ANALYSIS OF LAND USE CHANGE IN SLAWI SUBDISTRICT, TEGAL REGENCY, 2014 - 2024 USING HIGH RESOLUTION SATELLITE IMAGERY DATA - Rakuasa, Heinrich; Nurul Achmadi , Panji (Yayasan Nuraini Ibrahim Mandiri, 2024)
This research aims to analyze land use change in Slawi Sub-district, Tegal Regency, from 2014 to 2024 using high-resolution satellite image data. This study used Worldview-2 high resolution satellite image data in 2014 and Geoeye-1 in 2024. This study was classified into 14 land use classes consisting of rivers, roads, railways, agriculture, green open space, other vegetation, industry, housing, government, public service facilities, trade services, transportation, defense and security and open land. The spatial analysis method was used to map changes in land area based on the main use classes such as agriculture, housing, and infrastructure. The results showed a significant decrease in agricultural land area as well as an increase in residential land area and infrastructure, reflecting the changing pattern of regional growth and development. In conclusion, an in-depth understanding of land use dynamics in Slawi Sub-district is important to support environmental management policies, natural resource conservation, and sustainable regional development in the future.